Miniaturized Ir/IrOx pH Sensor for Quantitative Diagnosis of Dental Caries. (2016) - Tabata, M.; Ratanaporncharoen, C.; Asano, A.; Kitasako, Y.; Ikeda, M.; Goda, T.; Matsumoto, A.; Tagami, J.; Miyahara, Y.
Abstract: Diagnosis of dental caries is one of the most basic skills for oral healthcare professionals; however, the detection methods are based on visually diagnosis, such as inspection, palpation, and X-ray imaging. Therefore, quantitative and objective diagnostic technique is needed[1] . The aim of this study is fabrication and evaluation of Iridium/Iridium Oxide (Ir/IrOx) pH sensor for quantitative diagnosis of dental caries. The potentiometric response to pH showed -57.4 mV/pH in evaluated pH range from 4 to 8, which demonstrated that our electrode possesses the excellent proton sensitivity (Nernst slope; -59.2 mV/pH). Based on the evaluation results of dental caries, we confirmed the possibility for quantitative diagnosis of dental caries using Ir/IrOx electrode based on the pH as an index.